ANALISIS PENGENDALIAN KUALITASDENGAN METODE SEVEN TOOLSPADA PT. GELURAN ADIKARYA - Regina Puspa Ayu Saputri; Masmira Kurniawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The importance of quality control and improvement for a product is crucial to ensure that a company can compete in the market. There are many ways to implement quality control, one of which is by applying the seven tools method, which involves analyzing using several quality control tools such as Pareto diagrams, Flow charts, Ishikawa diagrams, Histograms, Check Sheets, and Control Charts. PT. Geluran Adikarya, a manufacturing company specializing in the production of fuel, LPG, and ART tanks, consistently implements quality control by checking each department, particularly in the welding and painting departments. This control is carried out by the quality control division in each department. The company always ensures the quality of its products before they move on to the next department, so that by the end of the production process, the company has produced defect-free products ready for distribution to consumers.